PELESTARIAN NILAI KEARIFAN LOKAL MELALUI UPACARA ADAT SEREN TAUN DI DESA CITOREK LEBAK BANTEN - Hidayat, Iman; Robandi, Babang; Nuryani, Pupun (Al-Mubtadi: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This paper aims to describe the preservation of local wisdom values in the traditional seren taun ceremony in Citorek Lebak Banten Village. local wisdom values through the traditional ceremony of seren taun in Citorek Lebak Village, Banten. the data collection process was pursued using a qualitative descriptive approach using ethnographic methods. The results of this study are that there are local wisdom values in the traditional seren taun ceremony which are related to current developments. in which there are several values, including: social values, values, morals, educational values, religious values and environmental values. These values are accommodated in the culture and traditions that exist in the village of Citorek Lebak, Banten.